Hypertension and Associated Demographic Factors among Chepang Adults in Nepal - Dhungel, Kshitiz Upadhyay; K.C., Agya (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Hypertension is one of the leading health problems globally. In developing countries like Nepal, the prevalence of hypertension is increasing yearly. This study aims to find the prevalence of hypertension and associated demographic factors among Chepang people, an indigenous ethnic group also known as one of the isolated tribal groups of Nepal. Material and Methods: It is a descriptive cross-sectional study performed in total of 324 respondent living in chepang community of Majbang-09 of Kalika Municipality. Semi structured questionnaire including socio-demographic, anthropometric measurement, 24 hour diet recall, and food frequency to explore dietary diversity information. Data entry and analysis was done using SPSS 20. Chi-Square test was used to measure the association between variables and was considered significant at p <0.05. Results: According to the study the 35.5% of the respondent were hypertensive and 50.3% of were pre-hypertensive. More than half of the respondent (58.3%) had normal BMI followed by (26.9%) of the respondent were overweight, (9.0%) of the respondent were under nutrition and (5.9%) of the respondent were obese. Among the respondent who had hypertension (60.7%) were above 60 years and the lowest (21.3%) were below 40 years. Conclusion: The socio demographic variables like age, sex, educational status, annual income and marital status were found to be significantly associated with hypertension.